1987
DOI: 10.1111/j.1095-8649.1987.tb05310.x
|View full text |Cite
|
Sign up to set email alerts
|

The immune response of the thick‐lipped grey mullet, Chelon labrosus (Risso, 1826), to metacercarial infections of Cryptocotyle lingua (Creplin, 1825)

Abstract: Grey mullet, Chelon labrosur, (60-IOOg) have been found to respond immunologically to Crypfocofyle lingua, following a single exposure to 20000 cercariae, by the production of humoral antibody, sensitized pronephric leucocytes and cytotoxic serum factors. Antibody titres measured by passive haemagglutination reached a peak at week 4 with a -log, titre of 16 f SE. 1 .O, and titres of 10.7 f S.E I .O were still recorded after 10 weeks at the termination of the experiment. Cercarial agglutination was found unreli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Although commercial vaccination against helminth parasites of fish has met with no success to date, the ability to elicit humoral antibodies against a variety of parasites, including D, spathaceum, is encouraging (Hines & Spira 1974;Goven, Dawe & Gratzek 1980;Woo 1987;Bortz et al 1984;Wood & Matthews 1987;Whyte et al 1987;Houghton et al 1988). Indeed, here we report that challenge of rainbow trout immunized with an antigen concentration of approximately 25 f^ig of protein (250 cercariae) induces approximately 70-80% reduction in the establishment of metacercariae in the lenses of immunized fish (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although commercial vaccination against helminth parasites of fish has met with no success to date, the ability to elicit humoral antibodies against a variety of parasites, including D, spathaceum, is encouraging (Hines & Spira 1974;Goven, Dawe & Gratzek 1980;Woo 1987;Bortz et al 1984;Wood & Matthews 1987;Whyte et al 1987;Houghton et al 1988). Indeed, here we report that challenge of rainbow trout immunized with an antigen concentration of approximately 25 f^ig of protein (250 cercariae) induces approximately 70-80% reduction in the establishment of metacercariae in the lenses of immunized fish (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The metacercariae of Cryptocotyle lingua encyst in the skin of mullet generating a capsule of host cell origin, which ensures a safe location in the exposed fish skin. Wood and Mathews [57] demonstrated that immune fish serum can kill cercariae, but encysted metacercariae were resistant to its action. The metacercariae of some Bucephalidae encyst in the liver of fish.…”
Section: Host Isolation or Anatomical Sequestrationmentioning
confidence: 98%
“…As gyrodactylids are seen to escape surface areas rich in mucous cells and macrophages during the response phase (Buchmann 1997, Buchmann & Bresciani 1998, Lindenstrnn & Buchmann 1998, it could be suggested that macrophages in the skin have some influence on the amount of complement and mucous cells in the fish skin and thereby affect the microenvironment of these ectoparasites. Some studies have shown that fish leucocytes are able to interact with both protozoans (Cross & Matthews 1993, Steinhagen & Hespe 1997 and metazoan parasites as cestodes (Sharp et al 1991, Hoole 1994, Taylor & Hoole 1995, Morley & Hoole 1997, digeneans (Wood & Matthews 1987, Whyte et al 1989, nematodes (Ramakrishna et al 1993) and acanthocephalans (Hamers et al 1992). The relationship between monogeneans and fish leucocytes is nonetheless still unknown.…”
Section: Introductionmentioning
confidence: 99%